FURODA PILGRIMS BUSINESS IN ISLAMIC MARKETING OVERVIEW - Mu'is, Ahmad; Farida, Lailatul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
Pilgrim is worship that obligation for rich Moslem. Pilgrims not only need knowledge and physic ability but also enough financial. Far distance from original country to Haramain, place, food and another facilities. Pilgrims is divided into two classification regular and special. If Furoda is inside of Special pilgrim. The problem is deeply different with Special hajj, the first. Arab Saudi Kingdom invitation and short time, second. Limited edition, third. No guarantee able to flight toward Haramain, Fourth. High cost, up to 20-30 000 us dollar, fifth. High demand. This paper direction to know how understand the travel of hajj and umrah business about Haji Furoda and correlation with Shariah Marketing (Islamic Economic). The method used is descriptive qualitative. Novelty rare paper discuss about Furoda Pilgrims in Islamic Economic side.